Some Vectors of Reforming of Economic Function of the Modern State - BOBROVNYK, Svitlana V.; SHEVCHENKO, Anatolij Ye.; KOTENKO, Tatiana V.; PANCHENKO, Victoria V.; VARYCH, Olha (Journal of Advanced Research in Law and Economics, 2019)
In article the main vectors of reforming of economic function of the modern state are investigated. Defining in this direction is properly also the ordered standard basis which provides the primary directions of economic activity of the state and other subjects of the economic relations, quality and efficiency of the legislation governing the economic relations, increase in level of investment activity of the state, stimulation of development and improvement of a banking system, expansion of tax base, the organization of innovative activity of the modern state is constructed.